ANALISIS EFISIENSI FAKTOR-FAKTOR PRODUKSI USAHATANI PADI SAWAH DALAM PROGRAM UPSUS PAJALE DI KECAMATAN SEKERNAN KABUPATEN MUARO JAMBI - Elwamendri; Maris Stella Sinaga, Liony; Kernalis, Emy (Universitas Jambi, 2019)
This study aims to determine (1) the effect of the use of production factors on the production of lowland rice farming in the Upsus Pajale and non Upsus programs and (2) the efficiency of the use of production factors on the production of lowland rice farming in the Upsus Pajale and non Upsus programs. To determine the effect of the use of production factors on the amount of rice production, Regression Analysis method is used. For technical efficiency the use of production factors in lowland rice farming is used in the Productivity Function model. This study took three sample villages, namely Sekernan Village, Pulau Kayu Aro Village, and Tunas Mudo Village which was determined purposively and the sampling of farmers using the Simple random sampling method. The results of this study indicate that the use of seed inputs, urea fertilizer, SP36 fertilizer, decis, round up, labor and land area together influence the production of rice farming. The factors of production that significantly affect the production (output) of the Upsus Pajale and non Upsus farmers are seeds, urea fertilizer, SP36 fertilizer, decis, and land area. The average value of technical efficiency in Upsus Pajale program farmers is 0.62 and for non-Upsus farmers is 0.29. This means that the level of efficiency of the Upsus program farmers is higher than that of non-Upsus farmers. The use of production factors in Upsus program farmers has been efficient while non Upsus farmers have not been efficient.